Comparing the Effect of Different Antibiotics in Frozen-Thawed Ram Sperm: Is It Possible to Avoid Their Addition? - Anel-Lopez, Luis; Riesco, Marta F.; Montes-Garrido, Rafael; Neila-Montero, Marta; Boixo, Juan C.; Chamorro, César; Ortega-Ferrusola, Cristina; Carvajal, Ana; Altonaga, Jose R.; de Paz, Paulino; Alvarez, Mercedes; Anel, Luis (Frontiers in Veterinary Science, 2021)
It is crucial to perform a deep study about the most extensively used antibiotics used in sperm extenders. Most of the protocols and concentrations used in ram are direct extrapolations from other species. It is important to establish species-specific antibiotic treatments to optimize their use and if it is possible to reduce the quantity. Previews studies have assessed some aspects of sperm quality in vitro, but this study aimed to go further and assess the effect of three different antibiotic treatments, which are the most extensively used, not only in sperm quality or assessing the inhibitory effect on bacterial growth but also assessing these important parameters of productivity such as fertility, prolificacy, fecundity, and sex-ratio during a freeze-thaw process. Gentamicyn (G) treatment showed the worst results, not only concerning sperm quality but also in the reproductive trials exhibiting a toxical effect at the experiment concentration, and being the most powerful inhibiting bacterial growth. For its part, Lincomicyn-spectinomycin (LS), showed similar results inhibiting bacterial growth but it did not show a detrimental effect either in sperm quality or in reproductive parameters. Penicillin-streptomycin (PS) showed good results in the sperm quality and in the reproductive in vivo trials, but it showed a very poor effect inhibiting bacterial growth probably due to some kind of antibiotic resistance. According to our results, there is not a significant positive relationship between the higher bacterial inhibitory activity of LS and PS samples, and the sperm quality respect Control samples (without antibiotics). In the case of G, which exhibited the most effective as antibacterial, we observed a toxic effect on sperm quality that could be translated on productivity parameters. Our results suggest that the bacterial contamination control in frozen-thawed semen may be possible without the use of antibiotics, although the effects of longer periods of cooling storage and different temperatures of storage need to be further investigated for animal semen. At this point, a reflection about a drastic reduction in the use of antibiotic treatments in sperm cryopreservation is mandatory, since, freezing conditions could keep sperm doses contamination within the levels recommended by regulatory health agencies.